Дано уравнение 2^x - a = √(4^x - a).
Возведём обе части в квадрат.
2^(2x) - 2a*2^x + a² = 2^(2x) - a. После сокращения имеем:
2a*2^x = a² + a,
2a*2^x = a(a + 1), делим обе части на 2а.
2^x = (a + 1)/2. Отсюда находим х как степень.
x = log(2,((a + 1)/2)).
Дано уравнение 2^x - a = √(4^x - a).
Возведём обе части в квадрат.
2^(2x) - 2a*2^x + a² = 2^(2x) - a. После сокращения имеем:
2a*2^x = a² + a,
2a*2^x = a(a + 1), делим обе части на 2а.
2^x = (a + 1)/2. Отсюда находим х как степень.
x = log(2,((a + 1)/2)).